Analysis of Application of Business Process Management Principles in The Development of Regional Financial Management Systems and Procedures in Indonesia - Deddi Nordiawan; Ayuningtyas Hertianti (Syntax Literate, 2022)
Systems and procedures are essential instruments for realizing an accountable regional financial management process. The document mandated by Government Regulation (PP) Number 12 of 2019 concerning Regional Financial Management contains business processes as guidelines for carrying out all financial procedures in a Regional Government. Therefore, the documents stipulated in the Regional Head Regulation must be prepared by taking into account the principles of Business Process Management (BPM) formulated by Vom Brocke et al. (2014). This case study explores the application of these principles and finds that BPM principles in the preparation of the System and Procedures (Sisdur) for regional financial management in Regional Governments in Indonesia have been implemented entirely with varying quality of implementation. These qualities are divided into three major parts: Principles that have worked quite well, principles that have worked but have not been maximized, and principles that have not worked well. This study also found momentum to reform the preparation of digital-based business processes based on the architecture developed by the Minister of Home Affairs Regulation Number 77 of 2020.